(untitled) (Proceedings of the YSU C: Geological and Geographical Sciences, 2025)
At all times, both quantitative and qualitative indicators of human potential or demographic situation have had an essential role in solving various state strategic and tactical problems. Along with other factors, the demographic situation has conditioned the socio-economic growth and development of countries, strengthe-ning of defense capabilities and increase in military potential. To achieve a favorable demographic situation, countries have implemented and continue to implement special demographic policies. In this sense, the Republic of Armenia is no exception, where various processes have influenced the formation of the demographic situation during the Post-Soviet period. Identifying the existing problems of the current demographic situation and pointing out relevant solutions are considered one of the priority directions for the prospective development and socio-economic growth of the Republic of Armenia. In this context, the formation of a favorable demographic situation and effective management is one of the important guarantees for creating a stable security system.